Wiley Encyclopedia of Biomedical Engineering 2006
DOI: 10.1002/9780471740360.ebs0159
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Transducers

Abstract: A transducer is a device that converts a measured object quantity into an electrical signal. Biomedical transducers are transducers with specific uses in biomedical applications, such as physiological measurement and patient monitoring, and in health care. The object quantities in biomedical measurements are physical and chemical quantities that reflect the physiological functions in a living body. Although some quantities, such as blood composition, can be determined from a sample extracted from the body, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The absence of a gold-standard technique for measuring the heterogenous distribution of retinal and choroidal blood flow precludes a simple in situ calibration. 23 In conclusion, the Brown Norway rat is a useful model to aid in the interpretation and validation of HRF flow measurements. Our results have confirmed that there is a significant amount of flow-related information in the HRF map obtained from the current instrument.…”
Section: Figurementioning
confidence: 96%
“…The absence of a gold-standard technique for measuring the heterogenous distribution of retinal and choroidal blood flow precludes a simple in situ calibration. 23 In conclusion, the Brown Norway rat is a useful model to aid in the interpretation and validation of HRF flow measurements. Our results have confirmed that there is a significant amount of flow-related information in the HRF map obtained from the current instrument.…”
Section: Figurementioning
confidence: 96%
“…In past years two main methods for breathing monitoring have been developed [3][4][5][6][7]. In the first method, the air flow is sensed while in the second one the breast dilatation is sensed.…”
Section: Breathing Monitoringmentioning
confidence: 99%
“…Based on the miniaturization and encapsulation technologies, a number of swallowable wireless telemetric devices appeared. These devices included the ability to measure temperature (CorTemp w ) (Togawa et al, 1997), pressure (Rigel Ltd) (Kingham et al, 1984;Thompson et al, 1980) and pH (Heidelberg and Bravo capsules) (Barrie et al, 1992;Pandolfino et al, 2003;Ruan et al, 2003) within the GI tract. A summary of these ingestible pills is given and listed in Table III.…”
Section: Wireless Capsule Sensormentioning
confidence: 99%